Determine the Compressive Strength of Calcium Silicate Bricks by Combined Nondestructive Method - Jiri Brozovsky (The Scientific World Journal)
The paper deals with the application of combined nondestructive method for assessment of compressive strength of calcium silicate bricks. In this case, it is a combination of the rebound hammer method and ultrasonic pulse method. Calibration relationships for determining compressive strength of calcium silicate bricks obtained from nondestructive parameter testing for the combined method as well as for the L-type Schmidt rebound hammer and ultrasonic pulse method are quoted here. Calibration relationships are known for their close correlation and are applicable in practice. The highest correlation between parameters from nondestructive measurement and predicted compressive strength is obtained using the SonReb combined nondestructive method. Combined nondestructive SonReb method was proved applicable for determination of compressive strength of calcium silicate bricks at checking tests in a production plant and for evaluation of bricks built in existing masonry structures.